Phanerochaete chrysosporium Burds INOCULATION TO IMPROVE THE PHYSICAL PROPERTIES OF KAPOK PULP - Wiwin Tyas Istikowati; Sri Nugroho Marsoem (Program Studi Kimia, Universitas Lambung Mangkurat, 2012)
White rot fungus are wood degrading organism able to decompose wood polymers; lignin, cellulose and hemicelluloses. Some species of white rot fungi decompose wood lignin over wood polysaccharides (e.g. cellulose), make it preferable for biopulping applications. A study of Phanerochaete chrysosporium Burds fungi inoculation to kapok chips was conducted to investigate the characteristics for the wood chips to be used as pulp and paper raw materials, as degradation level influences pulp characteristic. Phanerochaete chrysosporium fungi was incubated at PDA for 10 days, then inoculated to kapok chips for 20, 30, and 40 days. Fiber morphology was analyzed furthermore 16% active alkali of kraft process was conducted for 1, 1.5, and 2 hours cooking times. The results showed that range of tear strength 4.23 mNm2/g up to 6.35 mNm2/g, tensile strength 35 N m/g until 39.9 N m/g and bursting strength 1,5 kPa up to 2,01 kPa. Key words : Biopulping, Phanerochaete chrysosporium, Ceiba pentandra, pulp and paper